Postoperative Orthopedic Surgical Site Infection Antibiogram of dr. Soebandi Hospital, Jember in 2019 - Nurul Indah Saffanah; Dini Agustina; Ika Rahmawati Sutejo (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2020)
Surgical site infection (SSI) is a microbial infection of the surgical wound within 30 days of operation or one year after surgery if an implant is placed in a patient. The incidence level of postoperative orthopedic SSI range to 71%. An increase in antibiotic-resistant bacteria causes the treatment of postoperative orthopedic surgical wound infections to be less effective, so there is an increase in morbidity, mortality, length of stay, and economic burden on hospital resources.Antibiogram were used to guidethe clinician and pharmacist selectedthe best empiric antimicrobial treatment in the event of pending microbiology culture and susceptibility results to overcome the disadvantages of antibotic-resistant bacteria. This study aimed to form a postoperative orthopedic SSI antibiogram of dr. Soebandi Hospital in Jember City, East Java, Indonesia which can be used as a reference to rational therapy. This study used a descriptive observational study research design with medical records from January – December 2019.A total of 34 isolates were found from 33 patients who did a culture examination. Of the 34 isolates, 25 were found to be positive for bacterial growth, while nine were negative. Twenty-two bacteria were Gram-negative and others were Gram-positive. The bacteria were tested against beta-lactam and non-beta lactam antibiotics.From antibiogram, showed that Gram-negative bacteria sensitive to the meropenem and resistant to cefotaxime. While, gram-positive bacteria showed sensitivity to doxycycline and resistant to erythromycin and penicillin.